B05 CAG profiling in R6/1 89Q indicates early and progressive expansion in critical neuronal populations and expansion and changes in surrounding glial cell populations. (29th August 2012) - Hirst, M; Vatsavayai, S; Dallerac, G; Milnerwood, A; Cummings, D; Rezaie, P; Evans, K; Stramek, A; Walters, S; Murphy, K
Abstract : Background: Localised CAG repeat expansion is a characteristic of both human HD and mouse model brains and could potentially contribute to the development of cellular dysfunction through the expression of progressively longer poly Q containing protein. A derivative of the R6/1 mouse expressing 89Q (Vatsavayai et al (2007) Brain Res. Bull) provides an ideal opportunity to assess expansion in an early, preclinical-like model. Aims: To characterise timing, extent and patterns of expression of somatically expanded CAG repeats in neuronal and glial cell populations of the cortico-striatal-nigral pathways, including white matter (corpus callosum), and to assess the extent of localised changes in glial cell populations in relation to phenotype development. Methods: PCR analysis of gDNA and mRNA isolated from cortico-striatal-nigral regions was used to provide an index of polyQ loading in cells from 2 to 20 months of age alongside determination of weight loss and motor phenotype onset. Additional glial and neuronal cell markers (transgene, GFAP, TH) were assessed in the first 12 months of age. Results: The 89Q phenotype is significantly milder than that seen in R6/1 116Q, with weight loss being a more robust marker of progression than motor deficits (clasping). mRNAs carrying expanded CAG repeats have been identified in neurons in the cortico-striatal-nigral axis by 2 months of age, being more extensive in striatal and substantia nigra neurons, well before any recorded phenotypic or electrophysiological deficits have been observed. Expansion profiles in both gDNA and mRNA indicate that regional and cell-specific differences are present. Expansion is extensive in glial cell populations and in corpus callosum and changes in cell markers suggest glial cell changes, although no evidence for activation is found. Conclusions: CAG expansion starts early and continues in all cortical-striatal-nigral neurons, indicating that these cells are exposed to transgenic protein carrying progressively longer polyglutamine tracts. The slow and more progressive development of phenotypic features in the 89Q mouse confirm that this animal presents an ideal opportunity to investigate early events that might represent presymptomatic or early Huntington's disease.